Minimally Invasive Transforaminal Lumbar Interbody Fusion With Intraoperative Fluoroscopy for Disc Space Preparation: Analysis of Fusion Rate and Clinical Results. Issue 5 (20th July 2020) - Lin, Guang-Xun; Sharma, Sagar; Rui, Gang; Song, Myung-Soo; Kim, Jin-Sung
Abstract: BACKGROUND: Meticulous disc space preparation is an important step toward ensuring arthrodesis in the interbody fusion procedure. Although minimally invasive techniques are becoming increasingly advanced in lumbar interbody fusion, concerns exist regarding adequate discectomy and sufficient endplate preparation from a transforaminal lumbar approach. OBJECTIVE: To describe the radiographic and clinical outcomes of single-level minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) using the intraoperative fluoroscopy-guided method for disc space preparation. METHODS: This is a retrospective study of 25 patients operated between June 2016 and Dec 2017. The radiographic outcomes included the intraoperative percentage of disc space preparation, fusion, and subsidence. Percentage of disc space preparation was calculated through intraoperative fluoroscopic imaging. Clinical outcomes included visual analog scale (VAS), Oswestry Disability Index (ODI), and satisfaction rate. RESULTS: Mean age of patients was 62.9 yr. The mean follow-up period was 22 mo. Mean extents of disc space preparation were 61.5% in the anteroposterior view and 80.3% in the lateral view. Fusion rates were 86% and 92% at 6 and 12-mo postoperatively, respectively. All patients showed clinical improvement according to VAS and ODI. CONCLUSION: MI-TLIF with intraoperative fluoroscopy-guided disc space preparation is shown to lead to potentially improved fusion rate. It is a safe and effective surgical method for degenerative lumbar disease. Additionally, in cases of cage subsidence caused by the endplate violation during disc space preparation, thorough sufficient bone grafting of the defect region avoids pseudoarthrosis. Graphical Abstract: